TBK1 phagosomal recruitment enhances antifungal immunity via positive feedback regulation with SRC - Yiting Feng; Xiaochen Cheng; Yuanzhe Yang; Chuanjin Liu; Yu Shi; Xiaopeng Qi; Wei Zhao; Bingyu Liu; Tian Chen; Chengjiang Gao (Cell Reports, 2025)
Summary: TANK-binding kinase 1 (TBK1) is a versatile serine/threonine protein kinase that is mainly recognized for its canonical role in antiviral immunity through interferon induction. Here, we report a previously uncharacterized function for TBK1 in antifungal defense. Using proteomic analysis, we identified TBK1 as a phagosome-directed protein after fungal infection, and biochemical analysis revealed that TBK1 is directly recruited to the phagosome by SHP2 in a process driven by SRC-mediated phosphorylation. This recruitment facilitates TBK1 aggregation and trans-autophosphorylation at the phagosome. Activated TBK1 then phosphorylates SRC at serine 17, a prerequisite for the full activation of SRC, thereby establishing a robust positive feedback loop among SRC, SHP2, and TBK1. Consistently, SRC-mediated antifungal signaling and production of proinflammatory cytokines and chemokines were significantly impaired in mouse bone marrow-derived macrophages (BMDMs) lacking TBK1. Myeloid Tbk1-deficient mice exhibited greater susceptibility to systemic Candida albicans infection. Overall, our findings reveal a critical role for TBK1 in antifungal immunity and highlight its potential as a therapeutic target for combating fungal pathogens.